2000
DOI: 10.3141/1709-14
|View full text |Cite
|
Sign up to set email alerts
|

Degree and Extent of Wetting Due to Capillary Rise in Soils

Abstract: Increased water content of subgrade soils can lead to degradation of their quality and result in pavement distress. Pavement performance depends on the modulus of the compacted unsaturated subgrade soil as well as that of the underlying natural soil deposits. The soil modulus is a strong function of water content; therefore, changes in water content over the life of the pavement must be understood. In this study, it has been found that for a relatively near-surface groundwater table, significant potential exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This was because the long period of rainfall before had allowed the water table to rise significantly and then began to fall with evaporation, despite this small rain. At the same time, the soil water content of the deep layers remained relatively stable for capillary rise [56,57]. When the rainfall increased to 17.5 mm ( Figure 5c) and 30.8 mm (Figure 5d), the water table rose by 0.065 m (5.2%) and 0.360 m (31.0%), respectively.…”
Section: Combined Effects Of Rainfall and Water Table Depth On Soil Wmentioning
confidence: 83%
See 2 more Smart Citations
“…This was because the long period of rainfall before had allowed the water table to rise significantly and then began to fall with evaporation, despite this small rain. At the same time, the soil water content of the deep layers remained relatively stable for capillary rise [56,57]. When the rainfall increased to 17.5 mm ( Figure 5c) and 30.8 mm (Figure 5d), the water table rose by 0.065 m (5.2%) and 0.360 m (31.0%), respectively.…”
Section: Combined Effects Of Rainfall and Water Table Depth On Soil Wmentioning
confidence: 83%
“…High values of soil water content were observed at the deeper soil layers and strong correlation between soil water content and the water table were found at a depth of around 100 cm. The capillary action is significant in this region and the height of this capillary rise can be quite substantial [56,57]. Table 3.…”
Section: Combined Effects Of Rainfall and Water Table Depth On Soil Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary water is an important factor inducing silt site erosion and collapse (Ma and Liu 2020). When silty soil is used as subgrade filling material, if it is subjected to groundwater capillarity, the water content of subgrade soil will change significantly, which will lead to the decrease of subgrade strength, and then, settlement and collapse may occur (Al-Samahiji et al 2000). Therefore, it is of great theoretical and practical significance to study the rising law of capillary water in silty soil.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the pore structure and particle gradation had a significant effect on the rise of capillary water. Al-Samahiji et al (2000) studied the change law of soil water content and the characteristics of pore water pressure, suction, and soil strength in the range of capillary water infiltration. Li et al (2018) tested the capillary water rise of 8 kinds of soils by vertical pipe method, and found that the maximum rise height mainly depended on the distribution of large pores, and put forward a new method to calculate the maximum capillary water rise height by using soil pore distribution function.…”
Section: Introductionmentioning
confidence: 99%